Religious coping, stress, and quality of life of Muslim university students in New Zealand - Gardner, Timothy M. (Mental health, religion & culture, 2014)
Most of the research on religious coping has been conducted with Christian participants from Western cultures, although in recent years increasingly more studies have been conducted with Muslim participants. For university students in Muslim countries, religiosity is positively correlated with a variety of indices of mental health and psychological well-being, but only a small number of studies investigated coping in Muslims living and studying in a non-Muslim country. The present study thus explored the relationship between perceived stress, quality of life (QOL), and religious coping in a sample of 114 Muslim university students in New Zealand. International Muslim students had higher levels of spirituality/religiousness than domestic Muslim students, and used more positive and negative religious coping methods. For international students, positive religious coping was positively related to QOL and lack of stress, while, for domestic students, negative religious coping was negatively related to the QOL and increased stress. This different pattern may relate to the ethnic background of the participants, and the results of the present study thus highlight that Muslims studying at universities overseas can certainly not be considered as a homogenous group.